2022
DOI: 10.3390/ijerph191912729
|View full text |Cite
|
Sign up to set email alerts
|

Resilience for Undergraduate Students: Development and Evaluation of a Theory-Driven, Evidence-Based and Learner Centered Digital Resilience Skills Enhancement (RISE) Program

Abstract: Protective factors that build students’ resilience are known. A six-week digital resilience training program was developed on the basis of theory, evidence, and contextual information. The feasibility study sought to evaluate the acceptability, appropriateness, demand, implementation, and limited efficacy of a digital resilience skills enhancement program for undergraduate students. A single group, pre-test, post-test, concurrent mixed methods design among 10 undergraduate students was conducted in one univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Student stress may stem from cognitive errors and irrational beliefs (41). The resilience program's focus on challenging self-defeating thoughts, examining hypotheses about oneself, others, and the world, gathering evidence regarding core beliefs, and exploring alternative explanations proves effective in alleviating various emotions such as stress (42,43). Furthermore, research has demonstrated a significant correlation between exam anxiety and emotion regulation, as well as psychological resilience in students (44).…”
Section: Discussionmentioning
confidence: 99%
“…Student stress may stem from cognitive errors and irrational beliefs (41). The resilience program's focus on challenging self-defeating thoughts, examining hypotheses about oneself, others, and the world, gathering evidence regarding core beliefs, and exploring alternative explanations proves effective in alleviating various emotions such as stress (42,43). Furthermore, research has demonstrated a significant correlation between exam anxiety and emotion regulation, as well as psychological resilience in students (44).…”
Section: Discussionmentioning
confidence: 99%
“…The self-developed program was based on established stress theories, such as Lazarus and Folkman [ 23 ], and current research on resilience and the effects of online training [ 24 , 25 , 26 , 27 , 28 ]. The participants in the experimental group (EG) received two emails per day, one in the morning and one in the evening, for 28 consecutive days.…”
Section: Methodsmentioning
confidence: 99%